(untitled) (Eurasian Research Bulletin, 2023)
This article gives a brief overview of the realia’s and their features. In particular, the article is devoted to the realities of a particular era and the role of public life in their translation. It is noteworthy that studying the translation of national realia’s helps to improve the practical and theoretical knowledge of translators, firstly, by identifying methods for expressing national identity in a work of art; Identification of errors and deficiencies that lead to a deeper understanding of the artistic content of the work.